2016
DOI: 10.1021/acs.nanolett.6b00806
|View full text |Cite
|
Sign up to set email alerts
|

UV Photosensing Characteristics of Nanowire-Based GaN/AlN Superlattices

Abstract: We have characterized the photodetection capabilities of single GaN nanowires incorporating 20 periods of AlN/GaN:Ge axial heterostructures enveloped in an AlN shell. Transmission electron microscopy confirms the absence of an additional GaN shell around the heterostructures. In the absence of a surface conduction channel, the incorporation of the heterostructure leads to a decrease of the dark current and an increase of the photosensitivity. A significant dispersion in the magnitude of dark currents for diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 42 publications
5
39
1
Order By: Relevance
“…Following the interpretation for the case of a single AlN insertion [20], the reverse current is associated to a leakage path through the barriers, involving a GaN shell, surface conduction or the coalescence of multiple wires [10]. Under forward bias, among the set of nanowires under study, we observe a strong dispersion of the dark current, varying from a few nanoamperes to microamperes at +1 V bias.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Following the interpretation for the case of a single AlN insertion [20], the reverse current is associated to a leakage path through the barriers, involving a GaN shell, surface conduction or the coalescence of multiple wires [10]. Under forward bias, among the set of nanowires under study, we observe a strong dispersion of the dark current, varying from a few nanoamperes to microamperes at +1 V bias.…”
Section: Resultssupporting
confidence: 54%
“…Nanowire photoconductors are characterized by high photocurrent gains, which can reach 10 6 , and strong spectral contrast above and below the bandgap. A general feature in nanowire photoconductors is the fact that the photocurrent scales sublinearly with the impinging laser power, which has been shown for single GaN nanowires regardless of the presence of heterostructures [6][7][8][9][10], as well as for nanowires of other material systems such as ZnTe [11], ZnO [12,13], InP [14], CuO [15], and GaAs [16]. This sublinearity of the response hampers the use of such devices for quantification of the radiant fluence, and restricts their application domain to digital detection.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their unique material properties, nanostructures of III-nitride materials have been of considerable interest for various applications including piezotronic sensing, ambient energy harvesting, nanostructurebased lighting and computing devices, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13] Numerous types of nitride nanostructures have been explored via either templateassisted or template-free fabrication methodologies. [14][15][16][17] In the template-assisted strategy, material growth is carried out on sacrificial nanostructured template materials such as carbon nanotubes, polymers, or anodic aluminum oxide (AAO).…”
Section: Introductionmentioning
confidence: 99%
“…The spectral response is dominated by the GaN sections of the nanowire, but the spectral contribution from the GaN wells, located in the 450-400 nm spectral range, can be resolved in photocurrent spectroscopy measurements performed at room temperature. The photoresponse drops significantly with decreasing temperature, which demonstrate that photogenerated carrier extraction is thermally assisted.Using a GaN/AlN (2.7 nm/ 5.3 nm) superlattice without GaN outer shell (seefigure 17), Lähnemann et al[89] showed a photocurrent that scaled sublinearly with the optical power. The spectral response clearly shows a sensitivity to wavelengths below 360−380 nm (cut-off associated to transitions to the first excited level in the quantum wells), and a rejection of longer wavelengths.…”
mentioning
confidence: 99%